Refining the emergence scenario of the invasive recombinant Tomato yellow leaf curl virus -IS76 - Jammes, Margaux; Urbino, Cica; Diouf, Mame Boucar; Peterschmitt, Michel (Virology (New York, N.Y.), 2023)
TYLCV-IS76, a unique recombinant between tomato yellow leaf curl virus (TYLCV) and tomato yellow leaf curl Sardinia virus (TYLCSV), has replaced its parental viruses in southern Morocco. To refine its emergence scenario, its fitness was monitored experimentally in conditions aiming at reproducing natural situations, i.e. superinfection of plants already infected with parental viruses and competition with other TYLCV/TYLCSV recombinants (LSRec) automatically generated in plants coinfected with TYLCV and TYLCSV. TYLCV-IS76 accumulated significantly more than parental viruses regardless of plant age and superinfection delay. Although TYLCV-IS76 and LSRec both accumulated more than parental viruses in laboratory conditions, LSRec were displaced by TYLCV-IS76 in nature like parental viruses were. TYLCV-IS76 did not exhibit any vector transmission advantage over LSRec and TYLCV the most competitive parental virus. Thus, it is apparently only in the plant compartment that the recombination event that generated TYLCV-IS76, induced the competitiveness advantage by which the last became first.